Taman-Halbinsel, Russische Föderation - Schlotzhauer, Udo (e-Forschungsberichte des DAI, 2023)
The international and multidisciplinary joint project in South Russia, initiated in 2006, changed the existing reconstruction of the ancient topography and geology of the Taman Peninsula. Furthermore, excavations in selected locations east of the strait of Kerč indicate that the Greek colonization probably had started further in the East than previously thought. Therefore, the process of Greek colonization in the Bosporus must be reconsidered not only in its dating but even more in its geographical extension.